Early Short-Course Corticosteroids in Hospitalized Patients With COVID-19. (19th May 2020) - Fadel, Raef; Morrison, Austin R; Vahia, Amit; Smith, Zachary R; Chaudhry, Zohra; Bhargava, Pallavi; Miller, Joseph; Kenney, Rachel M; Alangaden, George; Ramesh, Mayur S
Abstract: Background: There is no proven antiviral or immunomodulatory therapy for coronavirus disease 2019 (COVID-19). The disease progression associated with the proinflammatory host response prompted us to examine the role of early corticosteroid therapy in patients with moderate to severe COVID-19. Methods: We conducted a single pretest, single posttest quasi-experiment in a multicenter health system in Michigan from 12 March to 27 March 2020. Adult patients with confirmed moderate to severe COVID were included. A protocol was implemented on 20 March 2020 using early, short-course, methylprednisolone 0.5 to 1 mg/kg/day divided in 2 intravenous doses for 3 days. Outcomes of standard of care (SOC) and early corticosteroid groups were evaluated, with a primary composite endpoint of escalation of care from ward to intensive care unit (ICU), new requirement for mechanical ventilation, and mortality. All patients had at least 14 days of follow-up. Results: We analyzed 213 eligible subjects, 81 (38%) and 132 (62%) in SOC and early corticosteroid groups, respectively. The composite endpoint occurred at a significantly lower rate in the early corticosteroid group (34.9% vs 54.3%, P = .005). This treatment effect was observed within each individual component of the composite endpoint. Significant reduction in median hospital length of stay was also observed in the early corticosteroid group (5 vs 8 days, P < .001). Multivariate regression analysis demonstrated an independent reduction in the composite endpoint at 14-days controlling for other factors (adjusted odds ratio: 0.41; 95% confidence interval, .22 – .77). Conclusions: An early short course of methylprednisolone in patients with moderate to severe COVID-19 reduced escalation of care and improved clinical outcomes. Clinical Trials Registration: NCT04374071. Abstract : In this multicenter quasi-experimental study of 213 patients, we demonstrate early short course of methylprednisolone in moderate to severe COVID-19 patients reduced the composite endpoint of escalation of care from ward to Intensive Care Unit, new requirement for mechanical ventilation, and mortality.